Experimental investigation the effects of mixture impoverished on the specific fuel consumption, engine performance and exhaust emissions a pre-combustion chamber gasoline engine - Bagirov, Hanlar; Can, Ibrahim; Oner, Cengiz; Sugozu, Ilker; Kapicioglu, Abdullah (Elsevier Sci Ltd, 2015)
In this study were investigation of the effect on exhaust gas emissions and the power cycle parameters change of changing the number of injector holes in pre-chamber a gasoline engine. In study 1, 2 and 3-hole injector used and the results were compared with conventional injection spray and flame ignition (ISFI) system engine. The formation of the different rates mixture in the cylinder, exhaust emissions and operate different effects on the parameters of the power cycle. This has been revealed by examining the change of the values experimentally. It has been try to constant of blowing severity fresh air into the pre combustion chamber, mix contents and other factors affecting combustion chamber. In addition, all changes made were to investigate the effects on the performance of the engine. In experiments standard injection engine with developed the pre-chamber engine were used and compared with each other. Positive results were obtained in emissions and engine performance values. (C) 2014 Energy Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: Pre-combustion chamber; Gasoline; Fuel spray; Direct injection